Pengaruh Biomassa Terhadap Efisiensi Boiler Pada Pembangkit CFB Batubara Dalam Sistem Co-firing - Kawiarso Kawiarso; Nuryoto Nuryoto; Anton Irawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The issue of global warming has gained widespread attention around the world. Warming of the atmosphere as a whole can be attributed mostly to the accumulation of more greenhouse gases (GHG). Coal is commonly used as a fuel source in steam power plants (PLTU), which results in a substantial CO2 gas emission when burned. Cofiring is a technology that allows palm shell biomass to be used as a fuel source in place of coal, which helps reduce greenhouse gas emissions and so slows down global warming. Cofiring trials including palm kernel shells (PKS, Palm Kernel Shell) are being conducted by PT. XYZ in Ciwandan, starting with 33% PKS, 67% PKS, and finally 100% PKS fuel. The examination of generation 2's performance looks at the impact of using coal fuel with cofiring palm shell biomass at the percentage stage. After using the indirect approach (ASME PTC-4), we find that while using coal as fuel, the boiler efficiency (HHV) is 86.27%, however when using PKS, it is only 83.33%. The boiler efficiency (HHV) is 86.30% when using PKS at a 33% cofiring ratio, and it drops to 83.62% when using PKS at a 67% cofiring ratio. It can be theoretically construed as a boiler because the efficiency increases with the use of 100% PKS fuel are still near to the efficiency of the boiler design (HHV = 89.39), and the effect of using biomass does not significantly affect the boiler's efficiency. which can now be used for combustion when fueled only by PKS biomass.